Analysis of the Export Volume of Temanggung Regency Against Inflation in Destination Countries - Dama Yuninata; Alfian Syahrul Grahita Utama (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study examines the effects of GDP per capita, population, and inflation on the export value of Temanggung Regency to its main destination countries. This study aims to understand how these macroeconomic factors influence regional export performance. Methodology: The study utilizes annual panel data from five main export destination countries during the period 2019-2022. The dependent variable is the export value of Temanggung Regency (in US$). The independent variables include the GDP per capita of Temanggung, the GDP per capita of the destination countries, the population of the destination countries, inflation in Temanggung, and inflation in the destination countries. Results: The panel regression analysis indicates that the GDP per capita of the destination countries has a negative relationship with Temanggung’s exports, although this effect is not statistically significant. Conclusions: This study concludes that the export volume of Temanggung Regency between 2019 and 2022 was primarily driven by the destination countries' population size, which exerted a positive and statistically significant impact, thereby confirming that large-scale market demand is a more critical determinant for regional exports than the individual wealth of those nations. Limitations: The study is constrained by a short observation period (2020-2 and a limited number of cross-sectional units (five destination countries), which may affect the generalizability of the results. Contributions: The findings can support local government and trade stakeholders in designing export promotion strategies and prioritizing destination markets.